Implementation of Grey Box Testing Technique in Testing the F1Math Application - Ang, Vincent; Rahman, Syaiful; Hasniati (STMIK KHARISMA Makassar, 2025)
The F1Math application was developed to assist students in learning mathematics through an interactive concept inspired by Formula 1 racing. This study aims to evaluate the effectiveness of the grey box testing technique in testing the F1Math application. The testing method used is grey box testing with a Regression testing approach, combining an analysis of the application's internal structure and observation of its external behavior. The testing process began with analyzing the system specifications and source code, followed by unit Testing, integration Testing, and regression Testing. User simulations across various game levels were also conducted. The results indicate that the grey box testing technique is effective in detecting bugs during the early stages of development. This approach accelerates the debugging process and enhances application stability, especially in critical areas such as gameplay features and mathematical calculations. In conclusion, the implementation of the grey box testing technique significantly contributes to improving the quality of the F1Math application. This approach successfully combines the strengths of code-based and user-behavior-based Testing, resulting in a more reliable and efficient application.